Sex/gender differences in service use patterns, clinical outcomes and mortality risk for adults with acquired brain injury: a retrospective cohort study (ABI-restart) - Georgina Mann; Lakkhina Troeung; Angelita Martini (Medical Journals Sweden, 2023)
Objective: To identify sex/gender differences in functional, psychosocial and service use patterns in community-based post-acute care for acquired brain injury.  Design: Retrospective cohort study. Subjects/patients: Adults with acquired brain injury enrolled in post-acute neurorehabilitation and disability support in Western Australia (n = 1,011). Methods: UK Functional Independence Measure and Functional Assessment Measure (FIM + FAM), Mayo-Portland Adaptability Inventory-4, goal attainment, length of stay (LOS), number of episodes of care and deaths were evaluated using routinely collected clinical and linked administrative data. Results: At admission, women were older (p < 0.001) and displayed poorer functional independence (FIM + FAM; p < 0.05) compared with men. At discharge, there were no differences in goal attainment, psychosocial function or functional independence between men and women. Both groups demonstrated functional gains; however, women demonstrated clinically significant gains (+ 15.1, p < 0.001) and men did not (+ 13.7, p < 0.001). Women and men had equivalent LOS (p = 0.205). Aboriginal and/or Torres Strait Islander status predicted longer LOS for women but not for men. Being partnered predicted reduced LOS for women but not men. Women had a higher risk of multiple episodes of care (p < 0.001), but not death (p = 0.409), compared with that of men. Conclusion: At admission to rehabilitation and disability support services for acquired brain injury, women have poorer functional independence and higher risk of multiple episodes of care, compared with men, suggesting greater disability in the community. By the time of discharge from these services, women and men make equivalent functional and psychosocial gains. The higher risk of multiple episodes of care for women relative to men suggest women may need additional post-discharge support, to avoid readmission.